Sex Differences in Portopulmonary Hypertension - DuBrock, Hilary M. (Chest, 2021)
BACKGROUND: Portopulmonary hypertension (POPH), pulmonary arterial hypertension that develops in the setting of portal hypertension, can lead to right-sided heart failure and death. Being female is a known risk factor for POPH, but little is known about the effect of sex on clinical manifestations, hemodynamics, treatment response, and survival. RESEARCH QUESTION: We sought to characterize sex differences in clinical characteristics, pulmonary hemodynamics, treatment response, and survival in patients with POPH. STUDY DESIGN AND METHODS: We performed a retrospective cohort study of adult candidates for liver transplant (LT) who had POPH within the Organ Procurement and Transplantation Network database. Females and males were compared. Multivariate regression was performed to assess the association between sex and pulmonary vascular resistance (PVR) and survival. Patients were also stratified by age (50 years) to determine how age modifies the relationship between sex and hemodynamics and survival. RESULTS: We included 190 adults (103 male, 87 female). Compared with men, women had a lower model for end-stage liver disease (MELD) score (12.1± 4.2 vs 13.8 ± 4.9; P = .01) and were more likely to have autoimmune liver disease. Women had a higher baseline PVR (610.6 ± 366.6 vs 461.0 ± 185.3 dynes-s-cm(−5); P < .001) and posttreatment PVR (244.6 ± 119.5 vs 202.0 ± 87.7 dynes-s-cm(−5); P = .008) and a greater treatment response (ΔPVR) (−359.3 ± 381.9 vs −260.2 ± 177.3 dynes-s-cm(−5); P = .03). In multivariate analysis, female sex (or gender) remained associated with a higher baseline PVR (P = .008). Women and men had overall similar survival (P > .05). When patients were stratified by age, being female was independently associated with worse waiting list survival after adjusting for MELD and PVR in younger patients (HR, 6.61; 95% CI, 1.25-35.08; P = .03) but not in older patients. INTERPRETATION: Compared with male candidates, female candidates for LT who had POPH had a higher PVR and lower MELD score and were more likely to have autoimmune liver disease. Women and men had similar overall survival, but female sex (or gender) was associated with worse survival in younger patients.